Adjustment of the US current account deficit - Mika Kortelainen (Bank of Finland, 2007)
We present a two country DGE model and estimate it using Bayesian techniques and euro area and US quarterly data for 1977 2004. In analysing the current accounts we find that a lower US rate of time preference or a higher dollar risk premium could render the deficit sustainable, but that these could push the interest rate to the zero bound. Secondly, we find that fiscal policy is not sufficiently effective to improve the current account although the zero bound is not hit.
URN:NBN:fi:bof-20140807111
Keywords: E61; F32; 330; current account; zero bound; policy coordination